Comparing translation accuracy in Belt and Road Malaysia children’s literature: Malay and Chinese native speakers vs ChatGPT - Lau, Yoke Lian; Yong, Zi Xian; Chia, Chen Eng; Yong, Zi Hong; Anna Lynn Abu Bakar; Ku Chen Jung @ Nur Alliyah Ku; Ernahwatikah Nasir; Bavani Arumugam (Bilingual Publishing Group, 2024)
The study investigates the translation processes of human and artificial intelligence translators in comparison. Human translators consist of a Chinese native speaker and belt and road translators. Different versions of artificial intelligence translators comprise ChatGPT 3.5 and ChatGPT 4.0. The research methodology employed is a keyword detection technique. One human translator and one translator powered by artificial intelligence achieved the highest scores in keyword detection, according to the results. Human translators continue to be indispensable in the field of translation, particularly in the translation of literary works. However, the research group is optimistic that artificial intelligence will soon be able to resolve this issue.